Key impact of finite-beta and fast ions in core and edge tokamak regions for the transition to advanced scenarios. (15th April 2015) - Garcia, J.; Challis, C.; Citrin, J.; Doerk, H.; Giruzzi, G.; Görler, T.; Jenko, F.; Maget, P.
Abstract: Extensive linear and non-linear gyrokinetic simulations and linear magnetohydrodynamic (MHD) analyses performed for JET hybrid discharges with improved confinement have shown that the large population of fast ions found in the plasma core under particular heating conditions has a strong impact on core microturbulence and edge MHD by reducing core ion heat fluxes and increasing pedestal pressure in a feedback mechanism. In the case of the ITER like wall, it is shown how this mechanism plays a decisive role for the transition to plasma regimes with improved confinement and it can explain the weak power degradation obtained in dedicated power scans. The mechanism is found to be highly dependent on plasma triangularity as it changes the balance between the improvement in the plasma core and the edge. The feedback mechanism can play a similar role in the ITER hybrid scenario as in the JET discharges analysed due to its high triangularity plasmas and the large amount of fast ions generated in the core by the heating systems and the alpha power.